Replicated evolutionary divergence in the cuticular hydrocarbon profile of male crickets associated with the loss of song in the Hawaiian archipelago. (16th September 2014) - Simmons, L. W.; Thomas, M. L.; Gray, B.; Zuk, M.
Abstract Female choice based on male secondary sexual traits is well documented, although the extent to which this selection can drive an evolutionary divergence in male traits among populations is less clear. Male field crickets Teleogryllus oceanicus attract females using a calling song and once contacted switch to courtship song to persuade them to mate. These crickets also secrete onto their cuticle a cocktail of long‐chained fatty acids or cuticular hydrocarbons (CHCs). Females choose among potential mates based on the structure of male acoustic signals and on the composition of male CHC profiles. Here, we utilize two naturally occurring mutations that have arisen independently on two Hawaiian islands and render the male silent to ask whether the evolutionary loss of acoustic signalling can drive an evolutionary divergence in the alternative signalling modality, male CHC profiles. QST‐FST comparisons revealed strong patterns of CHC divergence among three populations of crickets on the islands of Hawaii, Oahu and Kauai. Contrasts between wild‐type and flatwing males on the islands of Oahu and Kauai indicated that variation in male CHC profiles within populations is associated with the loss of acoustic signalling; flatwing males had a relatively low abundance of long‐chained CHCs relative to the short‐chained CHCs that females find attractive. Given their dual functions in desiccation resistance and sexual signalling, insect CHCs may be particularly important traits for reproductive isolation and ultimately speciation.